Hydrate-Bearing Sediment Imaging of Ghost Reflection in Vertical Cable Seismic Data Using Seismic Interferometry. (25th September 2022) - Wang, Linfei; Wang, Zhong; Liu, Huaishan; Zhang, Jin; Xing, Lei; Yin, Yanxin
Abstract : Marine vertical cable seismic (VCS) collects seismic waves by hydrophone array vertically suspended in seawater to prospect the offshore geological structure and monitor the reservoir. Due to its irregular source-receiver geometry, the primary imaging has narrow illustration coverage. Here, we proposed a cross-correlation transformation based on ghost wave interferometry. This method can transform the ghost reflections from the vertical cable seismic profile into the virtual surface seismic primaries just like those excited by the source and recorded by marine seismic towed-streamer below sea surface. After processing these virtual primaries with conventional method, we can obtain the ghost reflection imaging section with high resolution which effectively extend the illustration footprints in the subsurface. By application of this transform, virtual primaries are generated from the first-order ghost reflections of the actual VCS data. Then, migration of these virtual primaries provides a high-resolution image of hydrate-bearing sediments.